Hostile environmental jolts, transaction set, and new business - Venkataraman, S.; VAN de VEN, Andrew H. (Journal of Business Venturing, 1998)
In this exploratory study, we examine empirically the effects of environmental jolts on the evolution of the set of relationships that entrepreneurs have with their customers and suppliers (which we call the transaction set). We believe that understanding how turbulence in the environment affects the ability of entrepreneurs to hold on to their existing relationships or to add new relationships is fundamental to understanding the evolution and growth of an organization from a start-up to a stable, wealth-creating enterprise in the long-run. Using longitudinal data spanning 7 to 10 years from five start-up firms, we investigate three questions on the connection between environmental jolts and changes in the transaction set of the firm. First, do environmental jolts during the early life of the firm induce significant reductions in the set of relationships of a new, small firm? Second, are entrepreneurs able to add new relationships in greater numbers than the exit of old relationships following a jolt? And, third, do start-ups enjoy a “honeymoon” period when environmental jolts do not induce significant reductions in the set of relationships after a jolt? Our study yielded several findings that may be of interest to entrepreneurs, academics, and incubator managers. First, environmental jolts have a significant impact on the exits of relationships from the transaction set of a new, small firm, but not necessarily on the entry of new relationships into the set. Thus, although liabilities of newness and small size seem to affect the ability of entrepreneurs to hold on to their existing relationships during environmental jolts, these jolts do not seem to affect the entrepreneur's ability to add ties, at least in the very early life of the firm. Second, the level of reduction after environmental jolts seems to be less severe during the early life and greatest during the adolescent period. Further, entries of new relationships decrease with each succeeding jolt. One implication of our findings is that environmental selection pressures are more severe after an incubation period, called the “honeymoon” period. A second implication of our findings is the way in which liability of adolescence manifests itself. The honeymoon does not provide incubation against exits of relationships. Rather, the incubation manifests itself in the form of the willingness of new customers and suppliers to join the entrepreneur's transaction set even during a jolt. However, this goodwill shown by new customers and suppliers decreases with each succeeding jolt, thus making the firm very vulnerable to failure during its adolescent phase of life. We believe our study emphasizes the role that chance plays in the early survival and growth of firms. Firms “lucky” to avoid hostile jolts after their honeymoon period will be in a better position to grow rapidly, other things being equal. Despite sound management and superior exercise of enterprise, jolts appear in the life of firms in a stochastic, often unpredictable fashion. Although, it is not clear that firms who have superior enterprise, ability, or slack are more likely to succeed than those who don't, what is clear is that the ability to survive and grow is seriously affected with each succeeding jolt, whatever the ability. If our findings and our inference from the findings are general, they have an important public policy implication for new, small companies. Conventional wisdom holds that given liabilities of newness and small size, incubator environments are best provided to start-up firms. We would recommend a different strategy. Incubator environments are best provided not at the start-up stage to new business, but at the adolescent stage. Incubators should be provided to companies that show during the honeymoon phase that their ideas and products have merit and that they can attract customers and investors to their venture. It is during the adolescent stage that firms are most vulnerable to environmental disturbances, and where ability may not be a sufficiently good discriminator between survival and failure.